The Organizational Communicator 4.0 in Times of Digital Transformation: Competencies, Tools, and Challenges - Cesibel Valdiviezo-Abad, Karen; Vega Puma, Ariana; Plaza Granda, Anahí (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This article analyses the profile of the organizational communicator in the era of digital transformation, identifying professional competencies, key technological tools and the challenges faced in the management of internal and external communication. The methodology has a qualitative approach, applying semi-structured interviews to 3 communication directors in organizations and 3 ceo's of communication and marketing agencies, in order to obtain a global overview. We found that the organizational communicator profile must be versatile, relying on digital tools and data to meet the objectives of the organization and the demands of digital transformation.